Feasibility, psychological outcomes and practical use of a stress-preventive leadership intervention in the workplace hospital: the results of a mixed-method phase-II study. Issue 2 (23rd February 2022) - Stuber, Felicitas; Seifried-Dübon, Tanja; Tsarouha, Elena; Rahmani Azad, Zahra; Erschens, Rebecca; Armbruster, Ines; Schnalzer, Susanne; Mulfinger, Nadine; Müller, Andreas; Angerer, Peter; Helaß, Madeleine; Maatouk, Imad; et al.
Abstract : Objectives: Hospitals are psychologically demanding workplaces with a need for context-specific stress-preventive leadership interventions. A stress-preventive interprofessional leadership intervention for middle management has been developed. This phase-II study investigates its feasibility and outcomes, including work-related stress, well-being and transformational leadership. Design: This is a mixed-methods study with three measure points (T0: baseline, T1: after the last training session, T2: 3-month follow-up). Additionally, focus groups were conducted to assess participants' change in everyday work. Setting: A tertiary hospital in Germany. Participants: N=93 leaders of different professions. Intervention: An interactive group setting intervention divided in five separate sessions ((1) self-care as a leader, (2) leadership attitudes and behaviour, (3) motives, needs and stressors of employees, (4) strengthen the resource 'team', (5) reflection and focus groups). The intervention was conducted between June 2018 and March 2020 in k=5 runs of the intervention. Outcome measures: Feasibility and acceptance were measured with a self-developed intervention specific questionnaire. Psychological outcomes were assessed with the following scales: work-related strain with the Irritation Scale, well-being with the WHO-5 Well-being Index and transformational leadership with the Questionnaire of Integrative Leadership. Results: After the intervention at T2, over 90% of participants reported that they would recommend the intervention to another coworker (92.1%, n=59) and all participants (n=64) were satisfied with the intervention and rated the intervention as practical relevant for their everyday work. Participants' self-rated cognitive irritation was reduced, whereas their well-being and transformational leadership behaviour were improved over time. Focus group discussions revealed that participants implemented intervention contents successfully in their everyday work. Conclusions: This intervention was feasible and showed first promising intraindividual changes in psychological outcomes. Participants confirmed its practical relevance. As a next step, the intervention will be evaluated as part of a multicentre—randomised controlled trial within the project SEEGEN (SEElische GEsundheit am Arbeitsplatz KrankeNhaus).